Ovarian differentiation and development in cachara Pseudoplatystoma fasciatum - Valentin, F. N.; Batlouni, S. R.; Nascimento, N. F.; Silva, R. C.; Manzini, B.; Hilbig, C. C.; Pereira-Santos, M.; Nakaghi, L S O (Wiley, 2016)
One thousand five hundred cachara or tiger shovelnose catfish Pseudoplatystoma fasciatum, obtained from induced reproduction, were used to determine the onset of ovarian differentiation and development and to record the main characteristics of this process. Samples were collected from 0 to 240 days post-fertilization (dpf) and the results classified into stages I-XII. Ovarian formation was histologically detected for the first time when juveniles measured mean ± s.d. 51·5 ± 8·3 mm total length (LT ) at 39-45 dpf (stages I-V), with intense somatic cell proliferation originating in the ovarian cavity. Both LT and age of fish had a positive correlation (P < 0·001) with ovarian differentiation, but LT showed a greater correlation (r(2)  = 0·95) than age (r(2)  = 0·85), especially during the initial stages of development. From stages VI to VII, the ovarian cavity was enlarged and undifferentiated oogonia were present. At stage VIII, small projections formed in the ovarian stroma towards the ventral region of the gonad (future ovarian lamellae) and the basal membrane and differentiated oogonia nests could be seen. At stages IX and X, the germ cells entered meiosis and folliculogenesis was completed by stages XI and XII, which can be considered late in comparison to other Siluriformes. This study has demonstrated that ovarian differentiation in P. fasciatum begins with an intense proliferation of squamous epithelial cells (somatic cells) during the early stages of development and that sex inversion protocols could, thus, be applied successfully before this period. Furthermore, the results have demonstrated that both size and age can influence gonad differentiation and development in this species.
Keywords: age; folliculogenesis; germ cells; size; somatic cells